Early transient intraocular pressure spike after cataract surgery in highly myopic cataract eyes and associated risk factors. Issue 8 (8th November 2019) - Zhu, Xiangjia; Qi, Jiao; He, Wenwen; Zhang, Shaohua; Zhang, Keke; Lu, Qiang; Lu, Yi
Abstract : Purpose: To investigate the incidence of the early transient intraocular pressure (IOP) spike after cataract surgery in eyes with highly myopic cataract (HMC) and associated risk factors. Methods: Consecutive patients treated with phacoemulsification were recruited. IOP was measured before and 1 day, 3 days, 1 week and 3 months after surgery. Axial length (AL) and anterior chamber depth (ACD) were recorded, and optic disc tilt, rotation and beta-zone peripapillary atrophy (β-PPA) were measured from fundus photographs taken 1 week after surgery. Backward stepwise multiple linear regression was used to investigate the risk factors for early transient IOP spike in the HMC group. Results: Finally, 94 eyes of 94 HMC patients and 67 eyes of 67 age-related cataract (ARC) controls were included in analysis. The incidence of early IOP spike was 10% in the ARC group and 28% in the HMC group (OR=3.277, p<0.05) at 1 day after surgery. In the HMC group with IOP spikes, more males were seen and affected eyes showed longer AL, shallower ACD, greater optic disc tilt, and larger β-PPA than those without (all p<0.05). Multivariate analysis showed that sex, AL, ACD, and area of β-PPA were significantly associated with an early transient IOP spike in HMC eyes (all p<0.05). Conclusions: Highly myopic eyes are more susceptible to early transient IOP spike after cataract surgery, and male sex, longer AL, shallower ACD, and greater β-PPA are associated risk factors. Clinical trial registration number: NCT02182921 .